Revisiting city public libraries a follow-up study on public city libraries' services for physically and visually handicapped - Cruz, Ma. Elvirita D. (2012)
"Among the four types of libraries, School, Academic, Special and Public libraries, Public libraries are considered to have the mandate to serve the information needs of the whole community. Public libraries as both social and educational institution must be able to provide free access to information and make it available to all without prejudice even to society's marginalized sector including persons with disabilities. Mobilizing public libraries to be agents of literacy and education for nation building should be the concern to create change that will minimize poverty. Equipping public libraries to be suitable for the needs of every member of the community including marginalized disable persons will enable them to be self-sufficient members of the community and the society at large. There have been previous studies conducted to assess the capacity of the Philippine public libraries to cater to the needs of persons with disabilities. In the study conducted by Angala (2001), factors such as facilities, equipment, collections, programs and staff's ability to attend to the needs of persons with disabilities were evaluated to determine what city public libraries were providing best services. His study was the point of referral of this study which sought to compare the above-mentioned factors for the span of ten years covering the years from 2001 to 2010, as well as the public libraries' current status, factors for improvement, constraints for progress and future plans. Nine of the selected city public libraries included in this study are the city public libraries of Caloocan, Las Piñas, Makati, Manila, Marikina, Parañaque, Pasay, Pasig, and Quezon City. The researcher used the descriptive method in presenting gathered data from library visits, interview, questionnaires and checklist. The findings of the study showed that there are no much significant improvements in city libraries' services to visually and physically handicap for the past ten years. The researcher found that (1) Public city libraries included in this study does not have special services for visually handicapped patrons but regards that regular services provided to able bodied clients already suffice the information needs of the physically handicapped users, (2) Most libraries do not consider providing library services for the blind primarily because of the absence of blind clients, (3) Most of the city public libraries do not have facilities that provide easy access to physically handicapped which are mandated by the law, (4) City public libraries provide regular services ti physically handicapped patrons to secure their psychological condition, (5) Providing library personnel with special training in handling visually and physically handicapped clients is still not given attention, (6) In a span of ten years, the only aspect where all libraries improved is the provision of Internet access which is not mainly aimed for persons with disabilities but for general public., (7) Outreach programs are not mainly aimed for people with visual and physical disability, (8) Problem with budget is not just about lack of funds but are often caused by low regard of the local government to libraries and librarians, (9) Though most libraries have desire to provide services to persons with disabilities, most of them do not see it as a priority, and (10) Only four out of nine city public libraries have a plan to provide special services to blind clients. "
Thesis (M.L.I.S.)--University of the Philippines, Diliman.
Keywords: Libraries and people with disabilities -- Philippines -- Manila Metropolitan Area; Public libraries -- Philippines -- Manila Metropolitan Area